Nonlinear distortion compensation algorithm aided by channel estimation of memoryless power amplifier for OTFS receiver - Zhanjun JIANG; Huan LIU; Huawei ZHANG; Cuiran LI (Tongxin xuebao)
A compensation algorithm for OTFS receiver was proposed to solve the problem of transmission signal distortion caused by the nonlinear characteristics of power amplifier (PA) in the orthogonal time frequency space (OTFS) system.The channel state information was estimated by Bussgang theorem combined with the complex coefficient polynomial of PA and the average energy of the distortion term.Based on it, the transmitted signal was reconstructed with distortion term and the estimated value was updated for the polynomial normalization.Furthermore, the iterative zero-forcing equalization algorithm was employed to complete adaptive compensation analysis of the nonlinear distortion at the receiver.The results show that the nonlinear influence on transmission signals is reduced, which caused by Saleh and Rapp models, and BER performance of OTFS system is improved effectively.